Global food value chains and obesity in low- and middle-income countries - Hashad, Reem; Lim, Sunghun; Abay, Kibrom A. (Elsevier, 2024)
Low- and middle-income countries (LMICs) are experiencing disproportional increases in overweight or obesity rates. Parallel to this trend, many LMICs are witnessing significant growth in their participation in global food value chains (GFVCs). This paper aims to shed light on the public health implications of increasing participation in GFVCs. Leveraging macro- and micro-level data spanning 25 years, we study the relationship between countries’ participation in GFVCs and women’s overweight or obesity rates. We explore heterogeneous implications by disaggregating countries’ participation into backward and forward linkages in GFVCs, as well as across rural and urban areas. We find that temporal increases in countries’ participation in GFVCs are significantly associated with increasing overweight or obesity rates, primarily when countries participate in backward linkages and for urban populations. Participation in GFVCs involving forward linkages appears to have negligible implications, and the relationship between participation in GFVCs and obesity disappears for rural women. Furthermore, we find that an increase in countries’ participation in GFVCs is associated with an increase in consumption of energy-dense foods such as sugar, commonly linked with obesity. Our findings have important implications for informing public policies aimed at addressing the increasing obesity rates and associated economic and health burdens in LMICs.